Interim Results of Rigicon Penile Prosthesis Implantation in a Single Center: The Largest Series in Türkiye - Muhammet İhsan Karaman; Rasim Güzel; Duygu Kirkik; Orhan Koca (Urology Research and Practice)
Objective: To analyze data from patient information forms (PIFs) submitted to the manufacturer of a new 3-piece inflatable penile prosthesis (IPP), the Rigicon Infla10® , to summarize interim outcomes of 250 implantations in a single center, which is the largest series in Türkiye.